Oligohydramnios and its perinatal outcome - Saxena, Rita; Patel, Brinda; Verma, Anjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Oligohydramnios is one of the major causes of perinatal morbidity and mortality. The sonographic diagnosis of oligohydramnios is usually based on an AFI≤5 cm or on a single deepest pocket of amniotic fluid≤2 cm3. Our study was aimed to study the perinatal outcome in oligohydramnios. Aim and objective were to study obstetric risk factors associated with oligohydramnios and maternal outcome in the form of mode of delivery, and to assess neonatal complications in terms of APGAR score at birth, NICU admission rates, meconium stained liquor and still birth rates. Methods: It was an Observational, Prospective, clinical study of 100 pregnant patients diagnosed with oligohydramnios by ultrasound, carried out in Geetanjali medical college and hospital, Udaipur for period of from January 2020-August 2020. The study was conducted after ethical clearance and with informed consent. Detailed history on demographic profile, medical illness, obstetric history and antenatal complication if any in the present pregnancy; general examination, obstetric examination and bimanual examination were performed meticulously. Results: In our study 53% cases of oligohydramnios were associated with some of the risk factors like PIH (29%), IUGR (22%), fetal anomaly (1%), systemic maternal disease (1%) and 47% of the cases were Idiopathic. LSCS was done in 85.71% cases with AFI<5 cm. Low birth weight was found in 51.43% cases with AFI<5 cm. NICU admission was required for 28.57% cases with AFI<5 cm. Conclusions: AFI is an important and convenient screening test for prediction of perinatal outcome. In presence of oligohydramnios, the risk of fetal distress, operative delivery, low Apgar score, low birth weight, perinatal morbidity and mortality are more. Hence early detection of oligohydramnios, associated antenatal risk factors and timely management can improve the maternal and fetal outcome.